Comparison experiment on the sputtering of EUROFER, RUSFER and CLAM steels by deuterium ions. (March 2022) - Arredondo, R.; Balden, M.; Schwarz-Selinger, T.; Höschen, T.; Dürbeck, T.; Hunger, K.; Schlueter, K.; Golubeva, A.; Wang, P.; Terentyev, D.; Jacob, W.
Highlights: EUROFER, RUSFER and CLAM steels exposed to mass-filtered, monoenergetic D ion beam. W surface enrichment and surface roughness observed after exposure in steel samples. Sputter yields determined via mass-loss and eroded layer thickness. D retention studied by He-3 nuclear reaction analysis and thermal desorption. Abstract: In this work, the RAFM steels EUROFER, RUSFER and CLAM, along with a reference pure Fe sample, were all exposed to the same source of deuterium and analyzed using the same techniques, allowing a direct comparison of the experimental results. A 200 eV/D mass-selected deuterium ion beam at the SIESTA facility was used to bombard the samples to a fluence of 5 × 10 24 D m −2 at 450 K. The surface morphology of the samples was investigated with Scanning Electron Microscopy. The sputter yield of the samples was determined by weight-loss measurements and confirmed by measurements of the eroded depth. The near-surface enrichment of W and Ta was investigated via Energy-dispersive X-ray spectroscopy, X-ray Photoelectron Spectroscopy and Rutherford Backscattering Spectrometry. Grain-orientation-dependent sputtering was studied with Confocal Laser Scanning Microscopy and Electron Backscatter Diffraction. Lastly, Nuclear Reaction Analysis and Thermal Desorption Spectrometry were employed to analyze deuterium retention in all the samples. The erosion behavior of all three steels under deuterium bombardment was confirmed to be similar. The measured sputter yield was comparable for all three steels, and significantly lower than that of pure Fe. Likewise, all steels develop a needle-like surface morphology under the given exposure conditions and a W- and Ta-enriched layer in the range of few nanometers, while the Fe sample remained smooth. Retained deuterium amounts were also comparable among the steel samples, and were overall larger than the retention measured for the pure Fe sample.